STRATEGI PEMASARAN DAN PENDAPATAN PRODUK TEH DAUN KELOR PADA KELOMPOK TANI USAHA MAJU BERSAMA DI DESA NOELBAKI KECAMATAN KUPAN TENGAH - Kristianus Ivan Agung; Ernantje Hendrik; Siska Elvani (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
This study aims to describe the marketing strategies applied by the Usaha Maju Bersama farmer group in Noelbaki Village and to analyze the income generated from moringa leaf tea farming. The research employed descriptive qualitative and quantitative methods, with SWOT analysis (IFAS and EFAS) to identify internal and external factors influencing marketing strategies, and cost– revenue analysis to measure farm income. The results show that marketing strategies include product, price, promotion, and distribution, with strengths in product quality but weaknesses in packaging and promotion. Opportunities arise from increasing consumer demand for herbal products, while threats include competition from similar products. Income analysis revealed that the business is economically feasible, with an annual net income of Rp 64,275,000. These findings highlight the need for improved digital promotion, packaging innovation, and distribution expansion to enhance competitiveness and sustainability.